VerboWeb 3.0: Decoding Verb Behavior in Brazilian Portuguese – From Lexical Semantics to Web-Verified Syntactic Patterns - Cançado, Márcia (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2025: Anais do XVI Simpósio Brasileiro de Tecnologia da Informação e da Linguagem HumanaDO - 10.5753/stil.2025.37862, 2025)
This paper introduces VerboWeb 3.0, a lexical-semantic and syntactic database of Brazilian Portuguese verbs. Building on previous releases, it catalogs over 2,000 lemmas and about 20,000 examples (in progress), organized into seven semantic categories and more than 65 classes. Each class is validated against web-attested sentences to ensure accuracy. A key innovation is flexible granularity, allowing verbs to belong to multiple overlapping classes. Classes have been reorganized to better reflect the structure of the BP verbal system. The user interface has been redesigned for intuitiveness and accessibility. VerboWeb 3.0 supports theoretical linguistics through argument structure analysis, provides training data for NLP tasks, and aids education by facilitating the creation of language exercises.